2020
DOI: 10.22271/chemi.2020.v8.i3n.9343
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of guava-papaya jam

Abstract: Guava-Papaya jam was developed and evaluated for changes in its physico-chemical, microbiological and sensory parameters at monthly interval for three months storage period. Total soluble solids increased significantly, while acidity decreased significantly in guava-papaya jam with the advancement in storage period. Yeast and mold count increased significantly in blended jam during storage. The colour and appearance, flavour, taste, mouthfeel and overall acceptability of guava-papaya jam decreased significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
2
7
0
2
Order By: Relevance
“…Chutney was prepared as described by many researchers [10][11][12][13] with some modifications as per the taste and practices of local people. Damaged and bruised fruits were sorted out.…”
Section: Preparation Of Chutneymentioning
confidence: 99%
See 1 more Smart Citation
“…Chutney was prepared as described by many researchers [10][11][12][13] with some modifications as per the taste and practices of local people. Damaged and bruised fruits were sorted out.…”
Section: Preparation Of Chutneymentioning
confidence: 99%
“…A lot of researches have been conducted depending upon the ethno-cultural variations. Curry leaf chutney powder [9], mango chutney [10], guava chutney [11], amala chutney [12] and guava-papaya chutney [13] were studied earlier. Excess amount of harvested amalas can be turned into higher value products with increased self-life.…”
Section: Introductionmentioning
confidence: 99%
“…Rahul et al (2019) studied sensory qualities of guava-jamun cheese and observed that cheese prepared with 20 per cent guava and 80 per cent jamun pulp blends was found most acceptable with respect to colour and appearance (8.20), flavour (8.10), texture (8.10), taste (8.10) and overall acceptability (8.12). Kumar et al (2019a) blended aonla-papaya pulp to form cheese blends (100:0, 80:20, 60:40, 40:60, 20:80 and 0:100) as per standard procedure.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…Most of the confectionery products are prepared from artificial flavour and concentrate of fruits, not directly from pulp that can be harmful for health, but fruit cheese is a product prepared from pulp or puree of sound ripe fruits, whether in fresh form, frozen or previously preserved, by cooking with nutritive sweeteners and salt to obtain a thick consistency so that it sets on cooling. It can be prepared from a single fruit or with mixed fruits (Kumar et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…O chutney é um molho agridoce preparado pela adição de frutas e/ou vegetais, açúcar, sal, vinagre, especiarias e ervas (Yadav, et al, 2020). Autores vem demonstrando que a utilização de frutas na elaboração de molhos é viável e contribui para prolongar a vida de prateleira desses vegetais, além de boa aceitabilidade e agregação de valor (Thakur, et al, 2018;Joshi, et al, 2017;Kumar, et al, 2020).…”
Section: Introductionunclassified